2017
DOI: 10.1002/ijc.30699
|View full text |Cite
|
Sign up to set email alerts
|

Dacomitinib‐induced diarrhoea is associated with altered gastrointestinal permeability and disruption in ileal histology in rats

Abstract: Dacomitinib-an irreversible pan-ErbB tyrosine kinase inhibitor (TKI)-causes diarrhoea in 75% of patients. Dacomitinib-induced diarrhoea has not previously been investigated and the mechanisms remain poorly understood. The present study aimed to develop an in-vitro and in-vivo model of dacomitinib-induced diarrhoea to investigate underlying mechanisms. T84 cells were treated with 1-4 μM dacomitinib and resistance and viability were measured using transepithelial electrical resistance (TEER) and XTT assays. Rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 33 publications
5
41
0
Order By: Relevance
“…This is the first study to compare functional in vivo permeability, and morphological assessment of tight junction proteins in the setting of dacomitinib‐induced gut toxicity. Our previous research has indicated that dacomitinib induces severe ileal damage and barrier dysfunction . This study further characterized this barrier dysfunction; showing increases in barrier permeability to 4 kDa FITC‐dextran, and clear changes to tight junction proteins.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This is the first study to compare functional in vivo permeability, and morphological assessment of tight junction proteins in the setting of dacomitinib‐induced gut toxicity. Our previous research has indicated that dacomitinib induces severe ileal damage and barrier dysfunction . This study further characterized this barrier dysfunction; showing increases in barrier permeability to 4 kDa FITC‐dextran, and clear changes to tight junction proteins.…”
Section: Discussionsupporting
confidence: 63%
“…FITC dextran was administered orally to measure gastrointestinal permeability. Serum FITC dextran levels were significantly elevated in rats of either treatment arm involving dacomitinib . Rats treated with dacomitinib alone had significantly elevated levels of serum FITC dextran compared with controls ( p = 0.0018), and crofelemer alone ( p = 0.0043).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations